KECOCOKAN KARATERISTIK PEKERJAAN DALAM MENINGKATKAN KINERJA PENDIDIK - Sih Darmi Astuti; Kusni Ingsih (Conference In Business, Accounting, And Management (CBAM), 2015)
This study investigated and analyzed the influence of skill variety and feed back of Job characteristics on teacher performances via job satisfaction and organizational commitment. The population of this research is Teacher of Early Childhood Education (Paud) Non-Formal in Rembang whereas 1.040 people. The tehnique is purposive sampling. This involves Paud teachers in Rembang Regency as sampling who have been employed for 3 years and achieved at least middle school (SLTP) graduated. The sample of this research 120 respondent. The methods of this research are linear regression and Path analysis. The study found to improve performance in 5 ways as follows: (1) feed back of job characteristics was direct influence on performance; (2) feed back also influence on performance and continuance commitment as mediation; (3) feed back was influence on performance and promotion of satisfaction as mediation; 4) feed back was influence on teacher performance and job satisfaction as mediation; and (5) skill variety influence on Teacher performance and job satisfaction as mediation. Â Keywords: skill variety, feed back, job satisfaction, organizational commitment, and performance